Angler Attitudes Explain Disparate Behavioral Reactions to Fishery Regulations. Issue 10 (19th June 2019) - Murphy, Robert; Scyphers, Steven; Gray, Steven; H. Grabowski, Jonathan
Abstract : Recreational fishery management poses unique challenges as diverse user groups often maintain disparate attitudes and behaviors, limiting our ability to predict how fishing mortality may change under future regulatory conditions. We surveyed Striped Bass Morone saxatilis anglers from multiple coastal Atlantic states to explore how potential policies may change fishing behavior, assess angler motivations and catch‐related attitudes, and determine whether attitudes correlate with intended behavior. Results revealed that rule changes fundamentally changed effort allocation, whereby participants often shifted fishing effort to other saltwater species. However, disparate groups of anglers responded quite differently to potential policies. Importantly, differences in participant attitudes about fishing, such as how much they value keeping fish, were important predictors of intended behavior. Overall, our study illustrates how behavior, and thus fishing mortality, may shift under future management scenarios, and that an understanding of the characteristics of recreational fishing populations may help to predict the directionality and magnitude of these changes.